Importance of Women in freedom struggle in India - M.P, Bhavya.P; Somashekar, Somashekar (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The historical development of indian freedom struggle would be mentioning the contribution of women the sacrifice made by the indian women . almost of occupational criteria . the freedom struggle women replete with the somany life sefering and sacrifice, selflessness. Braveness women many of us dono’t know that there were hundreds of women who stronger of male countreparts. They fought with true spirit and courage. The indian women broke away from various restrictions and got out of their traditional home and other orientated roles and responsibilities. So the particularly participation of women to fight as warrior’s in male dominating society. Extradinary and unmesurable of in women to fight as warrior’s in the male dominating and household society. Moreover, female not only sacrifice their lives but also combat such issues rani laxmi bhai was one of such women who fought against british role by mitigating all odds hence paper entitle to highlight the historical develop and struggle in period of freedom.